2008
DOI: 10.1111/j.1467-9531.2008.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

2. Measurement Error in Stylized and Diary Data on Time Use

Abstract: We investigate the nature of measurement error in time-use data. Analysis of "stylized" recall questionnaire estimates and diarybased estimates of housework time from the same respondents of a British survey gives evidence of systematic biases in the stylized estimates and large random errors in both types of estimates. We examine the effect of these measurement problems on three common types of statistical analyses in which the time-use variable is used as: (1) a dependent variable, (2) an explanatory variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 13 publications
2
120
0
3
Order By: Relevance
“…Parents of young children are an extremely time stressed subgroup, given the extra time spent on child care and housework (Craig and Mullan, 2010). Kan and Pudney (2007) also pointed out that the systematic error in ''stylized'' methods, including web surveys, was particularly significant for women with dependent children, which is a big proportion of our study population. Future studies should consider the high workload and thus potential high attrition in this subgroup, and minimize participants' burden as much as possible.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents of young children are an extremely time stressed subgroup, given the extra time spent on child care and housework (Craig and Mullan, 2010). Kan and Pudney (2007) also pointed out that the systematic error in ''stylized'' methods, including web surveys, was particularly significant for women with dependent children, which is a big proportion of our study population. Future studies should consider the high workload and thus potential high attrition in this subgroup, and minimize participants' burden as much as possible.…”
Section: Limitationsmentioning
confidence: 99%
“…A few studies have employed web surveys to collect timeuse data (Kan and Pudney, 2007), but the information on the reliability and efficiency of web surveys used for this purpose is still very limited (Juster et al, 2003). Kan and Pudney (2007) reported that ''stylized'' methods, including web surveys, are subject to larger random measurement errors and additional systematic errors compared with diary-based methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time diaries are typically seen as an accurate representation of people's real behavior. Accordingly, previous research has focused on the comparison of time use information collected using common survey questions and time diaries (Kan & Pudney 2007;Plewis, Creeser, & Mooney 1990). …”
Section: Measurement Instruments -A Literature Reviewmentioning
confidence: 99%
“…Where comparative data on the feasibility of time use methods does not seem to exist at all, data abound on the comparative accuracy of time use methods, particularly the question of stylized questions versus time diaries (Juster, Ono, and Stafford 2003;Kan and Pudney 2008;Frazis and Stewart 2012). This research generally tends to favor time diaries, noting the presence of greater systematic error in estimates based on stylized questions.…”
mentioning
confidence: 99%